2016
DOI: 10.1130/g37639.1
|View full text |Cite
|
Sign up to set email alerts
|

Solute sources and geochemical processes in Subglacial Lake Whillans, West Antarctica

Abstract: Subglacial Lake Whillans (SLW), West Antarctica, is an active component of the subglacial hydrological network located beneath 800 m of ice. The fill and drain behavior of SLW leads to long (years to decades) water residence times relative to those in mountain glacier systems. Here, we present the aqueous geochemistry of the SLW water column and pore waters from a 38-cm-long sediment core. Stable isotopes indicate that the water is primarily sourced from basal-ice melt with a minor contribution from seawater t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(94 citation statements)
references
References 32 publications
5
89
0
Order By: Relevance
“…It has been a very gratifying experience to see all these pieces of work over the years fall into a bigger and more coherent picture as our knowledge base expands. Alex Michaud, who was a graduate student of John Priscu and Mark Skidmore, also noted that the sea water component of solute in the sediment increased down core, consistent with sea salt and other solute diffusing out of the sediment into the lake water (Michaud et al, 2016). Figure 10.3 Concentration and carbon isotope composition of CH 4 in the sediment beneath Subglacial Lake Whillans.…”
Section: Microbial Life In Subglacial Lake Whillansmentioning
confidence: 89%
See 1 more Smart Citation
“…It has been a very gratifying experience to see all these pieces of work over the years fall into a bigger and more coherent picture as our knowledge base expands. Alex Michaud, who was a graduate student of John Priscu and Mark Skidmore, also noted that the sea water component of solute in the sediment increased down core, consistent with sea salt and other solute diffusing out of the sediment into the lake water (Michaud et al, 2016). Figure 10.3 Concentration and carbon isotope composition of CH 4 in the sediment beneath Subglacial Lake Whillans.…”
Section: Microbial Life In Subglacial Lake Whillansmentioning
confidence: 89%
“…Carbonation of silicates and sulphide oxidation were invoked as the principal weathering reactions, and the locus of the biogeochemical weathering reactions was felt to be in the fine-grained sediment in the lake floor, where pore water concentrations were much higher than concentrations in the lake waters, implying that solute diffused out of the sediment into the lake. This idea was explored in greater detail in a subsequent paper (Michaud et al, 2016), where ion exchange was felt to be the mechanism that removed Ca 2+ from the pore waters, relative to that anticipated from sea water concentrations. These observations were similar to those made by Jemma Wadham, based on her work at Finsterwalderbreen (Wadham et al, 2000), which suggested that ion exchange occurred in subglacial sediments.…”
Section: Microbial Life In Subglacial Lake Whillansmentioning
confidence: 99%
“…Outflow from SLW flows beneath the Whillans Ice Stream and drains into the ocean beneath the Ross Ice Shelf, and the lake is refilled by periodic inflow from upstream (Siegfried et al, 2014); the ice surface rises and falls with the lake level (Fricker et al, 2007). Microbiological analyses of water and sediment samples from SLW revealed the presence of active microbial communities and evidence for an ecosystem driven by chemosynthetic production (Christner et al, 2014; Mikucki et al, 2015; Achberger et al, 2016) and by organic matter and nutrients contained in relict marine sediments beneath the West Antarctic Ice Sheet (Scherer et al, 1998; Wadham et al, 2012; Michaud et al, 2016). This evidence, coupled with the connectivity of SLW to the hydrological network of this region (Fricker et al, 2007), suggests microbial life is widespread beneath the ice sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Upon access to the lake, instruments deployed measured the water column at ~1.5 m. Samples of water and sediment were taken, and returned to the surface for both immediate inspection and transfer to laboratories in the US. They showed that water within Lake Whillans contained "metabolically active" microorganisms, and that it was derived primarily from glacial ice melt with a minor component of seawater (Christner, 2014;Michaud et al, 2016) making it unique among known subglacial environments within Antarctica.…”
Section: Lake Whillansmentioning
confidence: 99%
“…The seawater influence is unlikely to be contemporary, as tidal pumping of modern ice-shelf-cavity sea water is limited to a distance of ~10km upstream of the grounding line, whereas Lake Whillans is ~100 km upstream (Michaud et al, 2016). An observed increase in the proportion of sea water with sediment depth suggests that Antarctic groundwater flow may well be important to Whillans ice stream dynamics, as has been demonstrated by numerical ice flow and hydrology modelling (Christoffersen et al, 2014).…”
Section: Lake Whillansmentioning
confidence: 99%